(untitled) (Scientific journal of the Fergana State University, 2026)
This article examines traditional methods and changes in the process of grain cultivation in the Khiva Khanate. Attempts to increase crop yields and, in turn, improve the income of the rural population in the late 19th and early 20th centuries are analyzed. The importance of technologies in agriculture, new crop varieties and methods of working with seeds are also considered. All this helps to bring about socio-economic changes in grain production in the Khiva Khanate’s agriculture. The article, based on the research conducted by the author, covers the economic, social and environmental aspects of grain crops.